RESEARCH OF THE MONUMENT OF ARCHITECTURE - CHILDREN'S BUILDING "CLINIC OF THE MEDICAL FACULTY OF THE UNIVERSITY" IN KHARKIV - Kreiser, I.; Chub, O.; Bastrakova, V. (Municipal economy of cities. Series: «Economy science», 2022)
The article raises the question of the study of architectural monuments of local importance in the city of Kharkiv. The end of the 19th – the beginning of the 20th century in the city of Kharkiv was marked by the development of industry, the expansion of the city, the construction of industrial and civil architecture objects. Today, the issue of preservation and restoration of historical and architectural heritage is more relevant than ever before. In connection with Russia's aggressive attack on Ukraine and the bombing of Kharkiv, there is a great need to study and research the past, namely this period. Kharkiv is gradually losing part of its history. The architecture of the late 19th and early 20th centuries is diverse in styles and directions. A large number of medical institutions of the specified period were built in the "brick" style – one of the directions of the broader and well-known phenomenon of eclecticism. In Kharkiv, a quarter of the Clinical Town of the famous architect A.K. Spiegel has been more or less preserved. The block also includes later buildings, close in terms of architecture and stylistic features to the "brick" style. The object of the study is one of the buildings included in the complex – the children's building "Clinic of the Medical Faculty of the University". Over the hundred years of its existence, this object changed its name several times, but always kept its purpose – to be a medical institution. The article pays much attention to the history of the complex and the building of the Children's Corps. An analysis of style, forms, architectural details and decoration was carried out. Interesting facts from the life and work of the architect A.K. Spiegel are presented.